A Thematic Interpretation of Selected Novels Of Tim O Brien - Azeez, Ahmed Saadoon; Benny, N Solomon (South Asian Journal of Social Sciences and Humanities, 2024)
Author from the United States who enlisted in the military during the Vietnam War. “The majority of his works are about Vietnam during the conflict, and his latter works often investigate the life of Vietnam soldiers after the war. O'Brien is perhaps most known for his book, which was published in 1990 and titled The Things They Carried. This book is a compilation of connected semi-autobiographical tales that were inspired by O'Brien's experiences during the war. The latter was referred to be " a masterpiece of modern war fiction" by The New York Times in the year 2010. Going For Cacciato, O'Brien's book about the conflict that was published in 1978 and won the National Book Prize, is another reason for the author's widespread reputation. In spite of the fact that O'Brien is most known for his writings on the Vietnam War, he is also highly regarded as a teacher and instructor of creative writing. From 2003 to 2012, he was the holder of an endowed chair in the Master of Fine Arts programme at Texas State University–San Marcos. The purpose of this article is to provide thematic interpretations on a selection of Tim O'Brien's works.”
Keywords: English literature; themes; Novels